2015
DOI: 10.1038/pr.2015.103
|View full text |Cite
|
Sign up to set email alerts
|

Mid-arm circumference is a reliable method to estimate adiposity in preterm and term infants

Abstract: Background: Premature birth is associated with increased adipose deposition after birth. Standard anthropometry (body weight, length, and head circumference) may not adequately assess fat deposition. Validated methods to assess adiposity are needed to optimize growth quality in preterm infants. The purpose of this study was to identify covariates of infant body fat. Methods: Air displacement plethysmography (ADP), standard anthropometry, and body circumferences were measured at hospital discharge in preterm (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 21 publications
1
19
0
3
Order By: Relevance
“…MUAC has been used extensively to assess nutritional status, mainly in malnourished areas of the world where it is used as a measure of lean muscle mass; it is used as a proxy measure of nutritional status and can be used when weight/height is not possible or appropriate and has been repeatedly validated for this purpose . MUAC has also been used in moderate preterm infants (born after 31‐week gestation) and term‐born infants at discharge from hospital, and has shown utility as a reproducible measure of growth and as proxy measure for adiposity in this less vulnerable group . Of note the SDS for weight between birth and discharge for infants in our study fell by a mean of just 0.69, equivalent to just over one marked centile on a UK‐WHO growth chart.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MUAC has been used extensively to assess nutritional status, mainly in malnourished areas of the world where it is used as a measure of lean muscle mass; it is used as a proxy measure of nutritional status and can be used when weight/height is not possible or appropriate and has been repeatedly validated for this purpose . MUAC has also been used in moderate preterm infants (born after 31‐week gestation) and term‐born infants at discharge from hospital, and has shown utility as a reproducible measure of growth and as proxy measure for adiposity in this less vulnerable group . Of note the SDS for weight between birth and discharge for infants in our study fell by a mean of just 0.69, equivalent to just over one marked centile on a UK‐WHO growth chart.…”
Section: Discussionmentioning
confidence: 99%
“…They have also been widely used in older children as a determinate of nutrition status and a proxy of lean mass . Two small studies have used MUAC in preterm infants , with the most recent of these by Daly‐Wolfe et al. , demonstrating some utility in estimating adiposity at discharge in moderately preterm infants (31–35 weeks gestation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Supra-iliac skinfold thickness and MAC measurements have shown to correlate reasonably with body fat measurements via ADP in preterm and term infants. 36 Thus, these measurements can be used as a simple and cost-effective method to assess body composition of infants when resources such as an ADP system are not available. Our study found that MAC decreased between 2 measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Simon et al 10 evidenciaram uma associação entre a baixa idade gestacional e a diminuição do escore-Z do peso durante a internação com um maior risco de déficit de massa livre de gordura. Apesar de as avaliações terem sido realizadas em momentos diferentes (alta hospitalar no estudo de Simon et al 10 e na idade gestacional corrigida de termo no nosso estudo), os resultados foram semelhantes, assim como os resultados do estudo de Daly-Wolfe et al 38 .…”
Section: I S C U S S ã Ounclassified